Use of thermal imaging in the evaluation of body surface temperature in various physiological states in patients with different body compositions and varying levels of physical activity - Monika Chudecka (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2013)
This is a review of thermal imaging methods used for the measurement of body surface temperatures, including the most important medical applications, papers on thermal maps of people with various body compositions, and the applicability of thermal imaging in sport training.